Monkeypox: a global health emergency - Stilpeanu, Ruxandra Ilinca; Stercu, Ana Maria; Stancu, Andreea Lucia; Tanca, Antoanela; Bucur, Octavian (Frontiers in Microbiology, 2023)
Over the past two years, the world has faced the impactful Coronavirus Disease 2019 (COVID-19) pandemic, with a visible shift in economy, medicine and beyond. As of recent times, the emergence of the monkeypox (mpox) virus infections and the growing number of infected cases has raised panic and fear among people, not only due to its resemblance to the now eradicated smallpox virus, but also because another potential pandemic could have catastrophic consequences, globally. However, studies of the smallpox virus performed in the past and wisdom gained from the COVID-19 pandemic are the two most helpful tools for humanity, that can prevent major outbreaks of the mpox virus, thus warding off another pandemic. Because smallpox and mpox are part of the same virus genus, the Orthopoxvirus genus, the structure and pathogenesis, as well as the transmission of both these 2 viruses are highly similar. Because of these similarities, antivirals and vaccines approved and licensed in the past for the smallpox virus are effective and could successfully treat and prevent a mpox virus infection. This review discusses the main components that outline this current global health issue raised by the mpox virus, by presenting it as a whole, and integrating aspects such as its structure, pathogenesis, clinical aspects, prevention and treatment options and how this ongoing phenomenon is being globally approached.